Parliamentary Oversight of Independent Regulatory Authorities in India. (September 2018) - Kumar, Surendra
Independent regulatory authorities have become an important component of the governance landscape in India and elsewhere. Some regulators have achieved useful outcomes in India. However, the creation of independent sectoral regulators in India has not been accompanied by critical reflection on their role, or attention to the political, legal and institutional contexts within which they operate. Lessons can be learnt from mature regulatory policy countries, such as the USA, the UK and Australia, that the regulatory environment needs to be constantly evaluated to make sure it is keeping pace with the changing technology, business environment and consumer needs and demands. Despite the number of bodies in India that are involved or responsible for regulatory reform, there is one function that seems to be missing and that is of a central oversight function. Most countries have an explicit whole of government regulatory policy and an oversight body, sometimes more than one, that is/are responsible for embedding some of the systemic tools across different parts of the government machinery.